2019
DOI: 10.1038/s41557-019-0210-4
|View full text |Cite
|
Sign up to set email alerts
|

Liquid–liquid phase separation during amphiphilic self-assembly

Abstract: DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
284
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 217 publications
(293 citation statements)
references
References 53 publications
6
284
0
3
Order By: Relevance
“…[40] Much work remains to ChemBioChem 2019ChemBioChem , 20,2553ChemBioChem -2568 www.chembiochem.org 2019 Wiley-VCH Verlag GmbH &Co. KGaA, Weinheim be done, but this study demonstrates that reversible coacervate-to-vesicle transformations could be used to promote spontaneous transfer of DNA from membrane-freet om embrane-bound compartments, andu ltimately to sustain genetic information replication through substrate uptake and waste disposal. [101] These studies therefore suggest that coacervate-to-vesicle transitions might be ag eneral phenomenon that could be extended to other building units. It is worth mentioning here that ar ecent study reported the transformation of polymer-based coacervate droplets into polymersomes throughc hanges in the ionic strength [100] (Figure 2I).…”
Section: Controlled Matter Exchangest Hrough Interfacial Membrane Assmentioning
confidence: 87%
“…[40] Much work remains to ChemBioChem 2019ChemBioChem , 20,2553ChemBioChem -2568 www.chembiochem.org 2019 Wiley-VCH Verlag GmbH &Co. KGaA, Weinheim be done, but this study demonstrates that reversible coacervate-to-vesicle transformations could be used to promote spontaneous transfer of DNA from membrane-freet om embrane-bound compartments, andu ltimately to sustain genetic information replication through substrate uptake and waste disposal. [101] These studies therefore suggest that coacervate-to-vesicle transitions might be ag eneral phenomenon that could be extended to other building units. It is worth mentioning here that ar ecent study reported the transformation of polymer-based coacervate droplets into polymersomes throughc hanges in the ionic strength [100] (Figure 2I).…”
Section: Controlled Matter Exchangest Hrough Interfacial Membrane Assmentioning
confidence: 87%
“…Liquids can enter the holder from one side through a plastic tube connected to the syringe and flow out from the same side through another plastic tube (Figure b‐ II ), allowing continued sample imaging under controllable liquid reaction conditions (Figure b‐ IV ). The flow rate of liquid could be adjusted by the syringe …”
Section: Construction Of In‐situ Temmentioning
confidence: 99%
“…Flüssig‐flüssig‐Phasenseparation (liquid‐liquid phase separation, LLPS) tritt in Zellen auf, spielt eine Rolle bei Infektionen und ist fundamental bei Selbstorganisationsprozessen von Amphiphilen . Andererseits werden flüssig‐flüssig separierte Vorstufenspezies in anorganischen Systemen, wie beispielsweise Oxidschmelzen und wässrigen Salzlösungen, gebildet.…”
Section: Figureunclassified